A 64-Year-Old Woman With Posttransplant Hepatitis. Issue 5 (September 2018) - Hardy, Naomi; Twaddell, William S.
Abstract : Abstract: Abnormal liver function tests and nonspecific histopathologic findings are relatively common in the post–liver transplant setting. Whereas some cases remain idiopathic and many resolve spontaneously, some carry a risk of chronicity and long-term liver dysfunction including cirrhosis, graft loss, and death. Accurate assessment and follow-up of such findings are therefore crucial in this population. We report a case of a 64-year-old woman who underwent liver transplantation for chronic hepatitis C infection with cirrhosis. Several months after transplantation, she underwent a liver biopsy as part of a workup for abnormal serologic studies and transaminase elevation. The biopsy showed nonspecific hepatitis. Eventually, additional serologic testing demonstrated hepatitis E viral infection. Causes of hepatitis and other forms of posttransplant liver disease, including hepatitis E, are discussed.